Diffusivity and hydrogenation of vanadyl porphyrins in the synthesized NiMo/Zr-SBA-15 and industrial NiMo/γ-Al2O3 catalysts. (2nd November 2022) - Chen, Zhentao; Wang, Bo; Yang, Haoxuan; Jiang, Tao; Yu, Jiahuan; Wu, Jianxun; Xu, Chunming
Highlights: Diffusion and hydrogenation of vanadyl porphyrins are studied by kinetic method. Diffusion makes a pronounced effect on HDV reactions of two porphyrins. VO-TPP receives more severe diffusion effect due to larger activity and resistance. Diffusion suffers larger hindrance in SBA-15 catalysts than theoretical prediction. HDV encounters a stronger diffusion limitation in Al2 O3 than SBA-15 based catalysts. Abstract: Hydrogenation reactions of two vanadyl porphyrins are performed over a series of NiMo/Zr-SBA-15 catalysts and an industrial NiMo/γ-Al2 O3 catalyst. The results validate that the diffusion of the porphyrins suffers significant hindrance in the catalyst pores, which make a pronounced effect on the reaction. The hydrogenation of vanadyl-TPP receives a much larger diffusion effect than vanadyl octaethylporphine, which attributes to its higher intrinsic activity and more severe diffusion resistance. The restrictive correlation indicates two vanadyl porphyrins are hindered more severely as diffusing through the orderly NiMo/Zr-SBA-15 catalysts than the theoretical prediction from the Renkin equation, which results from the non-spherical configuration of the reactants and simultaneous counter diffusion of the products. Hydrogenation reactions of the vanadyl porphyrins encounter a stronger internal diffusion restriction in the NiMo/γ-Al2 O3 catalyst than in the NiMo/Zr-SBA-15 catalysts, attributing to the random structure of the γ-Al2 O3 support.